IMPROVE SERVICE USER SATISFACTION AT THE INTERNATIONAL AIRPORT THROUGH FACILITIES AND QUALITY OF SERVICE - Euis Saribanon; Rista Dwi Pratiwi; Chaidir Tasran (ABNUS Publisher, 2021)
The research objective is to determine whether there is an influence of facilities and quality of domestic terminal services on service user satisfaction at El Tari Kupang International Airport in 2020. To answer the problem the author uses quantitative methods with primary data using questionnaire distribution and data management using regressionanalysis techniques, analysis coefficient data, multiple correlation, significant correlation test, coefficient of determination, and hypothesis testing. The results of this study are the facilities and quality of domestic terminal services jointly affect service user satisfaction shown by the multiple regression equation Y = 7.169 + 0.214 X1 + 0.594 X2, the regression equation shows there is an effect if the facilities and quality of domestic terminal servicestogether increased service user satisfaction at El Tari Kupang International Airport will increase with a strongrelationship. The strength of the relationship between these variables is positive and is at a strong level indicated by the coefficient of multiple correlation R = 0.799. The contribution of facilities and quality of domestic terminal servicestogether affect service user satisfaction by 63.8%. This means that 63.8% of the value of service user satisfaction isdetermined by the facilities and service quality of the domestic terminal together. Whereas for the remaining 36.2%service user satisfaction is influenced by other factors not examined in this study.